Answer:
D.) x = 7
Explanation:
4x - 9x + 3 = -32
The first thing we do is combine like terms which means to add or subtract or multiply or divide any numbers that are known. Here in this equation we have 4x and - 9x
4x - 9x + 3 = -32
- 5x + 3 = - 32
Now what we do is subtract the common numeral from the side where the x value is.
- 5x + 3 = - 32
- 3. - 3
- 5x = - 35
Lastly, we divide here we take the value next to x and divide both numbers, here we will divide by - 5.
- 5x = - 35
- 5x / - 5 = x
- 35 / - 5 = 7
Now we take are two solutions and create are final solution.
x = 7